Submental Flap as a Reconstructive Option for Reconstruction in Oral Cancer - Ahmed, Tahir Masood; Qayyum, Muhammad Umar; Tahir, Umamah; Tahir, Yumna; Zahra, Rubbab; Tahir, Maliha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To demonstrate the advantages and oncological safety of the submental flap. Study Design: Case series. Place and Duration of Study: Department of Plastic and Reconstructive Study, Combined Military Hospital Rawalpindi, Multan and Peshawar Pakistan, from Jul 2014 to May 2020. Methodology: Twenty patients underwent flap reconstruction with a submental flap. The patients were diagnosed with squamous cell carcinoma, basal cell carcinoma and verrucous carcinoma at different sites of the head and neck. Only patients with no cervical lymph node metastasis were included. Results: We operated a total of 20 patients, out of which 11 (55%) were male and 9 (45%) were female. The mean age was 62.75 years (range: 47-80 years). Thirteen (65%) patients were diagnosed with Squamous cell carcinoma, 5 (25%) with Basal cell carcinoma and 2 (10%) were diagnosed with Verrucous carcinoma on histopathology. Two (10%) patients reported back with regional recurrence and were given postoperative radiotherapy. One (5%) patient had complete flap loss while 2 (10%) had distal tip necrosis. Conclusion: In carefully selected cases submental flap is a viable option, without the risk of occult metastasis.